(untitled) (Comprehensive Journal of Science, 2025)
This study aimed to identify the role of e-governance in enhancing the competitiveness of Libyan commercial banks from the perspective of customers of bank branches in the city of Zawiya. The study adopted the descriptive-analytical approach and used a questionnaire as the main tool for data collection from a random sample of 235 customers of Jumhouria Bank and Wahda Bank. The study examined four dimensions of e-governance: discipline, transparency, accountability, and responsibility. The results revealed a relatively high level of e-governance implementation in the banks under study and showed a statistically significant relationship between the dimensions of e-governance and competitiveness. Responsibility ranked first, followed by transparency, accountability, and finally discipline. The study recommended improving technological infrastructure, training employees, and expanding the use of modern electronic tools in order to improve banking services and strengthen the competitiveness of Libyan commercial banks.